ANALISIS PENGARUH KETETAPAN HARGA, PROMOSI, DAN FASILITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI HOTEL YESTOYA WAY JEPARA LAMPUNG TIMUR - Buchori Buchori (Derivatif : Jurnal Manajemen, 2015)
Companies that are able to compete in the market is the company that can provide quality products or services. So the company is required to continue to make improvements, especially in the quality of service. It is intended that all the goods or services being offered will have a good place in the eyes of the public as consumers and potential consumers. Because consumers in selecting goods and services based on the motivation that will affect the type, taste the goods and services purchased.Formulation of the problem in this research is "Are there statutes influence price, promotion, and service facilities on consumer satisfaction in Hotel Yestoya Way Jepara East Lampung in 2014?"The purpose of this study was to determine and analyze the effect of statutes price, promotion, and service facilities on consumer satisfaction in Hotel Yestoya Way Jepara East Lampung in 2014.The populations in this study are all consumers who stay at the Hotel Yestoya Way Jepara East Lampung during 2014.Results of the study conclude from this study that the purpose of statutes price, promotion, and service facilities affects customer satisfaction. Results of analysis that has been done by using multiple linear regression formula above, found that the provisions pricing, promotion, and service facilities affects only 0.784 whereas 0.216 influenced by other factors. Therefore both the independent variable is affecting, but the requirements are smaller than these three variables. Thus statutes price, promotion and service facilities affects customer satisfaction at the Hotel Yestoya Way Jepara East Lampung. Keywords: Consumer satisfaction, price, promotion, service facilities.